Surgeon Oriented Preoperative Radiologic Evaluation in Cochlear Implantation - Our experience with a Proposed Checklist - Mandour,Mahmoud (2019)
Abstract Introduction Preoperative temporal bone imaging studies have been routinely performed prior to cochlear implantation. Radiologists need to report these examinations with special focus on the surgeon’s expectations. Objectives To provide a basic structured format, in the form of a checklist, for reporting preoperative computed tomography (CT) and to its clinical impact on operative findings. Methods The preoperative temporal bone CT scans of 47 patients were analyzed and reported according to the proposed checklist. Intraoperative assessment of mastoidectomy, posterior tympanotomy and round window access was done by the surgeon in a blinded fashion and were correlated with the radiological findings to assess its significance. Results The proposed radiological checklist was reliable in assessing operative difficulty during cochlear implantation. Contracted mastoid and lower tegmen position were associated with a greater difficulty of the cortical mastoidectomy. Presence of an air cell around the facial nerve (FN) was predictive of easier facial recess access exposure. Facial nerve location and posterior external auditory canal (EAC) wall inclination were predictive of difficult round window (RW) accessibility. Conclusion Certain parameters on the preoperative temporal bone CT scan may be useful in predicting potential difficulties encountered during the key steps involved in cochlear implant surgery.